Visual outcomes with two posterior chamber phakic intraocular lenses in myopic patients: a contralateral eye study - Li, Boliang; Chen, Xun; Cheng, Mingrui; Lin, I-Chun; Jiang, Yinjie; Lei, Yadi; Xu, Guanghan; Li, Mingwei; Mao, Zhiwei; Zhou, Xingtao; Wang, Xiaoying (Frontiers in Medicine, 2025)
PurposeAssess the efficacy, safety, and visual quality of two posterior chamber phakic intraocular lenses (PIOL) for myopia correction.MethodsIn this randomized double-blind prospective controlled trial, 38 eyes of 19 myopic patients received phakic refractive (PR) IOL in one eye and implantable collamer lens (EVO ICL) in the opposite eye and were followed up for 1 year. Uncorrected distance visual acuity, corrected distance visual acuity, vault, disk halo size, contrast sensitivity, higher-order aberrations, retinal imaging quality, intraocular scattering, and subjective glare/halo perception were measured.ResultsAt 1 year, mean efficacy indices were 1.03 ± 0.16 (PR) and 1.01 ± 0.15 (ICL), and mean safety indices were 1.18 ± 0.07 (PR) and 1.15 ± 0.09 (ICL). The PR group had lower vaults than those of the ICL group at 1 year (342.63 ± 153.94 vs. 470.00 ± 230.31 μm, P = 0.010). One month postoperatively, the severity of glare/halo was significantly milder in the PR group than that in the ICL group (P = 0.035). However, 1 year postoperatively, no significant differences were observed in the severity of glare/halo between the two groups.ConclusionPhakic refractive implantation is a safe and effective treatment option for myopia. The PR group exhibited lower vaults than those of the ICL group. The PR group had milder glare/halo in the early postoperative period compared to the ICL group, though long-term differences were not significant.